2016
DOI: 10.3390/f7080162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships between Socioeconomic Background and Urban Greenery in Portland, OR

Abstract: Do urban residents experience societal benefits derived from urban forests equitably? We conducted a broad-scale spatial analysis of the relationship between urban greenery and socioeconomic factors in the Portland metropolitan area. The Normalized Difference Vegetation Index was derived from National Agriculture Imagery Program images to map urban vegetation cover, and Outdoor Recreation and Conservation Area data were used to identify green spaces. These measures of urban greenery were correlated with census… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 46 publications
0
21
0
2
Order By: Relevance
“…Resultados significativos con p < 0.05. tanto la cantidad de árboles (Brown, 2012) como su diversidad, área de copa y otros atributos estructurales (Escobedo et al, 2015), son mayores en los estratos más altos. De manera similar, este patrón de mayor abundancia y calidad de la infraestructura verde en las zonas con mejor condición socioeconómica, ha sido observado en otras ciudades de Latinoamérica (De la Maza et al, 2002;Pedlowski et al, 2002;Escobedo et al, 2016), Norteamérica (Schwarz et al, 2015;Nesbitt y Meitner, 2016) y Europa (Kabisch y Haase, 2014). Teniendo en cuenta que los estratos socioeconómicos buscan capturar las diferencias socioeconómicas de la población (Hernández, 2016), los resultados obtenidos indican problemas de inequidad ambiental en Bogotá, tal como han concluido previamente otros autores (Brown, 2012;Escobedo et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Resultados significativos con p < 0.05. tanto la cantidad de árboles (Brown, 2012) como su diversidad, área de copa y otros atributos estructurales (Escobedo et al, 2015), son mayores en los estratos más altos. De manera similar, este patrón de mayor abundancia y calidad de la infraestructura verde en las zonas con mejor condición socioeconómica, ha sido observado en otras ciudades de Latinoamérica (De la Maza et al, 2002;Pedlowski et al, 2002;Escobedo et al, 2016), Norteamérica (Schwarz et al, 2015;Nesbitt y Meitner, 2016) y Europa (Kabisch y Haase, 2014). Teniendo en cuenta que los estratos socioeconómicos buscan capturar las diferencias socioeconómicas de la población (Hernández, 2016), los resultados obtenidos indican problemas de inequidad ambiental en Bogotá, tal como han concluido previamente otros autores (Brown, 2012;Escobedo et al, 2015).…”
Section: Discussionunclassified
“…Aunque la importancia del acceso a la vegetación urbana y sus servicios ecosistémicos es ampliamente reconocida, hay pruebas que demuestran que su distribución no es equitativa en muchas ciudades del mundo (Kabisch y Haase, 2014;Schwarz et al, 2015;Nesbitt y Meitner, 2016). Factores socioeconómicos como los ingresos monetarios, características étnicas y raciales, género, entre otros, han sido identificados como limitantes de la disponibilidad de coberturas vegetales urbanas tanto en cantidad como en calidad.…”
Section: Introductionunclassified
“…The study found that forest loss was due to the increase in urban population and the forest drying induced by climate change, but this trend has not occurred in the rural setting. Nesbitt and Meitner (2016) found a high correlation between vegetation cover and population density, house age, income, and race respectively and the importance of different measures of access to urban forest.…”
Section: Environment and Socio-economic Indicatorsmentioning
confidence: 94%
“…We observe that many authors define justice, or its corollary concepts of inequality and inequity, in terms of the equal distribution of its benefits among all groups of urban residents [35,37,38,40,45]. Some studies go beyond this spatial notion of justice to include time.…”
Section: Recognitionmentioning
confidence: 99%